2012
DOI: 10.1016/j.ajo.2011.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Biomarkers of Oxidative Stress and Genetic Variants in Age-Related Macular Degeneration

Abstract: Purpose To compare plasma levels of oxidative stress biomarkers in patients with age-related macular degeneration (AMD) and controls and to evaluate a potential relationship between biochemical markers of oxidative stress and AMD susceptibility genotypes. Design Prospective case-control study Methods Plasma levels of oxidative stress biomarkers were determined in 77 AMD patients and 75 controls recruited from a clinical practice. Cysteine (Cys), cystine (CySS), glutathione (GSH), isoprostane (IsoP), and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 61 publications
1
31
0
Order By: Relevance
“…The increased levels of arachidonic acid in sera of AMD patients compared with controls suggest that AMD patients may have more substrate for generation of F2-isoP than controls. 40 In a clinic-based casecontrol study involving 77 AMD patients and 75 controls, Brantley et al 24 found no significant association between plasma levels F2-IsoPs and AMD. Similarly, in the Beaver Dam Eye Study, Klein et al 23 reported that plasma levels of eight isoprostanes were not associated with 15-year cumulative incidence of AMD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increased levels of arachidonic acid in sera of AMD patients compared with controls suggest that AMD patients may have more substrate for generation of F2-isoP than controls. 40 In a clinic-based casecontrol study involving 77 AMD patients and 75 controls, Brantley et al 24 found no significant association between plasma levels F2-IsoPs and AMD. Similarly, in the Beaver Dam Eye Study, Klein et al 23 reported that plasma levels of eight isoprostanes were not associated with 15-year cumulative incidence of AMD.…”
Section: Discussionmentioning
confidence: 99%
“…Few previous studies have examined the association of isoprostanes in plasma with AMD. 23,24,40 In a case-control study evaluating the role of serum lipids in AMD, Orban et al 40 analyzed serum lipids from 21 Japanese patients affected by neovascular AMD and 24 controls. Authors found the levels of docosahexaenoic acid, arachidonic acid, and their ratios were significantly different in AMD patients than controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esterified IsoF also form in the liver after carbon tetrachloride poisoning (Song et al, 2008). Plasma levels of unesterified IsoF, which likely reflect at least to some extent changes in esterified IsoF in tissue, are elevated in age-related macular degeneration, severe sepsis, mercury exposure, acute kidney injury, and preterm resuscitation (Alkazemi et al, 2013; Billings et al, 2011; Brantley et al, 2012; Montine et al, 2004; Vento et al, 2009; Ware et al, 2011). …”
Section: Class Iii: Oxpl With Cyclized Acyl Chainsmentioning
confidence: 99%
“…Table 1 depicts the S/N ratio for lipid concentrations in the range 100 pM , C , 1 mM. Conservatively interpreting these data indicates that the LOD of the current system is approximately 1-10 pM, a range acceptable for fluorescence-based assay development and easily competent for the determination of circulating plasma biomarkers [39][40][41]. For example, millimolar lipid and protein levels and micromolar vitamin concentrations in plasma were used by Karaouzene et al [42] to determine that obesity induces both oxidative stress and lipid composition changes in men.…”
Section: System Limit Of Detectionmentioning
confidence: 99%